Efficacy and Safety of Intralesional Hyaluronic Acid versus Control or Verapamil in Acute-Phase Peyronie’s Disease: A Systematic Review - Jundi, Abdur Rahman Faqih Al; Danarto, Raden; Budiono, Nur (Chakra Brahmanda Lentera Institute, 2026)
Background: Acute-phase Peyronie’s disease (PD) is challenging to treat because management is often delayed until the stable phase. Evidence for conservative therapies remains limited, and no previous systematic review has specifically evaluated intralesional hyaluronic acid (HA). This systematic review evaluates the efficacy and safety of intralesional HA compared with control or verapamil in acute-phase PD. Methods: This review was conducted in accordance with the PRISMA 2020 guidelines and registered. Six databases (PubMed, ProQuest, SAGE Journals, EBSCOhost, EuropePMC, and Wiley Online Library) were searched from inception, and trial registries were screened for ongoing studies. Two reviewers independently screened titles, abstracts, and full texts against pre-specified PICOS eligibility criteria, with disagreements resolved by a third reviewer. Eligible prospective trials (randomised and non-randomised) reported on penile curvature, plaque size or volume, erectile function (International Index of Erectile Function, IIEF), penile pain (Visual Analogue Scale, VAS), or patient-reported outcomes. Risk of bias was assessed in duplicate using the Cochrane Risk of Bias 2.0 (RoB 2.0) tool for randomised and the Risk Of Bias In Non-randomised Studies of Interventions (ROBINS-I) tool for non-randomised studies, and the certainty of evidence was rated using GRADE. Results: The search identified 287 records; after duplicate removal, 193 were screened and 23 full texts assessed, of which four prospective studies (two randomised controlled trials and two non-randomised prospective studies; 582 patients) met the inclusion criteria. The two RCTs were rated at low overall risk of bias (RoB 2.0) and the two non-randomised studies at moderate overall risk of bias (ROBINS-I), mainly owing to confounding and participant selection. Intralesional HA was associated with improvements in penile curvature (reductions of approximately 4.6–9.5° versus control or verapamil, including a 9.01° [46.1%] reduction versus an untreated control), plaque size or volume (up to a 93.7% reduction in plaque volume versus progressive growth in untreated patients), and erectile function (IIEF gains of approximately 1.0–3.8 points). HA showed a favourable safety profile with no major adverse events. However, several outcomes—including plaque-size reduction and IIEF change in some trials—did not reach statistical significance over verapamil, and the evidence base is small and clinically heterogeneous. Conclusion: Intralesional HA is a potentially effective, non-surgical option for acute-phase PD, yielding improvements in curvature, plaque size, pain, and erectile function with an excellent safety profile. However, the overall certainty of evidence is limited by the small number of included studies, methodological heterogeneity, and short follow-up; findings should therefore be interpreted with caution. Large-scale, multicentre RCTs with standardised protocols, extended follow-up, and evaluation of combination therapies (e.g., with phosphodiesterase-5 inhibitors) are required before HA can be integrated into clinical guidelines.